Suitable thicknesses of base metal and interlayer, and evolution of phases for Ag/Sn/Ag transient liquid-phase joints used for power die attachment - Li, Jianfeng; Agyakwa, Pearl; Johnson, Christopher Mark (Springer, 2014)
Both real Si insulated gate bipolar transistors (IGBT) with conventional Ni\Ag metallization and a dummy Si die with thickened Ni\Ag metallization have been bonded on Ag foils electroplated with 2.7 m and 6.8 m thick Sn as an interlayer at 250ºC for 0 min, 40 min and 640 min. From microstructure characterization of the resulting joints, suitable thicknesses are suggested for the Ag base metal and the Sn interlayer for Ag/Sn/Ag transient liquid phase (TLP) joints used in power die attachment, and the diffusivities of Ag and Sn in the Ag phase are extracted. In combination with the kinetic constants of Ag3Sn growth and diffusivities of Ag and Sn in Ag reported in the literature, the extracted diffusivities of Ag and Sn in Ag phase are also used to simulate and predict the diffusion-controlled growth and evolution of phases in the Ag/Sn/Ag TLP joints during an extended bonding process and in service.